Numerical simulation of optimal inlet air temperature of a forced convective fish cabinet rotary dryer - Emmanuel Obiani Akari; Ibrahim Ademola Fetuga; Olabode Thomas Olakoyejo; Manasseh Babale Shitta; Omotayo Oluwatusin; Joshua Kolawole Gbegudu; Antonio Marcos de Oliveira Siqueira (The Journal of Engineering and Exact Sciences)
Computational fluid dynamics was applied in the prediction of the effect of inlet temperature on the drying time of fish in a cabinet rotary dryer. On completion of the simulation, the temperature distribution of the air (fluid domain) within the drier at different inlet air temperatures and time intervals was obtained. Inlet air temperatures ranging from 35oC to 55oC was simulated for a time interval of 10 minutes to 120 minutes so as to examine the influence of inlet temperature on the drying process of fish. Based on this temperature range, it was observed that the ideal drying time for the fish which satisfies the condition for efficient fish drying for all five inlet air temperatures of the fish is 70 minutes. Furthermore, it can be observed that it takes about 120 minutes for the inlet air temperature of 50 degrees Celsius to attain a cabinet drying temperature of 316K (43°C) while it takes only 70 minutes for the inlet air temperature of 55 degrees Celsius to attain the same temperature under the same condition.